Physicochemical and electrochemical characterization of Nafion-type membranes with embedded silica nanoparticles: Effect of functionalization. (20th February 2021) - Porozhnyy, M.V.; Shkirskaya, S.A.; Butylskii, D.Yu.; Dotsenko, V.V.; Safronova, E.Yu.; Yaroslavtsev, A.B.; Deabate, S.; Huguet, P.; Nikonenko, V.V.
Abstract: Introduction of nanoparticles in membranes allows a significant enhancement of their performance in energy production, water treatment and other applications. However, the effect of nanoparticles' surface functionalization and the mechanism of their impact on membrane properties remain poorly studied. In this paper, we examine a Nafion-based membrane and its modifications, each containing 3 wt% SiO2 . The effect of functionalization by propyl, 3-aminopropyl and 3, 3, 3-trifluoropropyl is investigated. The water uptake, contact angle, conductivity, diffusion permeability to NaCl, current-voltage curves (CVC), chronopotentiograms (ChP), and the difference between the pH of the desalination compartment output and input solutions (characterizing the water splitting rate) are reported. It is found that the doping of the membranes with nanoparticles leads to increasing their conductivity in all cases except 3-aminopropyl, which imparts a positive charge to the nanoparticles; the diffusion permeability decreases and permselectivity increases in all cases. The latter is explained by transformation of the mesoporous membrane structure to the microporous one. The impact of nanoparticles on the membrane conductivity, CVC and ChP is mainly caused by an additional (positive) space charge introduced into the pore solution and at the membrane surface by the electric double layer surrounding the nanoparticles. The greater the surface charge density of the nanoparticles and the smaller their size, the stronger the impact. Accordingly, the highest conductivity, current density at a low fixed voltage and chronopotentiometric transition time are shown by the sample doped with SiO2 and 3, 3, 3-trifluoropropyl. The interplay between electroconvection and water splitting phenomena is discussed.